Axisymmetric problem for a spherical crack on the interface of elastic media - Martynenko, Michail; Lebedeva, Irina (My University, 2006)
A problem concerning a spherical interfacial crack is solved by the eigenfunction method. The problem is reduced to a coupled system of dual-series equations in terms of Legendre functions and then to a system of singular integral equations for two unknown functions. The behaviour of the solution near the edge of the spherical crack, and the stress-intensity factors and crack-opening displacement are studied. The case when the crack surfaces are under normal internal pressure of constant intensity is examined.
Keywords: двокомпонентний матеріал; двухкомпонентный материал; cavity; сферична тріщина; коефіцієнти інтенсивності напружень; розкриття тріщини; composite; elastic; inclusion; interface spherical crack; кафедра вищої математики імені проф. Можара В. І.